PENGARUH KOMPENSASI, MOTIVASI, DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI PTDI-STTD KABUPATEN BEKASI DIVISI FUNGSIONAL UMUM - Wendy Hidayatulloh; Denta Ananda (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
This research was conducted to find out the influence of Compensation, Motivation, and Communication on the Performance of PTDI-STTD Employees, Bekasi District, General Functional Division. This research uses quantitative research methods with a causality approach. The study used saturated sampling. The respondents used were as many as 80 employees of PTDI-STTD general functional division. In this study conducted the dissemination of questionnaires. The result of this study is that the variable Compensation and motivation individually do not have a significant influence on employee performance while communication has a significant influence on employee performance Keywords: Compensation, Motivation, Communication and Employee Performance